Occupational Safety and Health (K3) Counseling about Education to Prevent Occupational Diseases that Can Attack Workers on the Kinara Boarding House Building Project - Achmad Wahdi; Dewi Retno Puspitosari; Devangga Darma Karingga; Anis Akhwan Dhafin; Rahmad Wahyudi (Journal of Community Engagement in Health, 2025)
According to data from the International Labor Organization (ILO), it is estimated that there are around 340 million work accidents and 160 million cases of occupational diseases (PAK) each year worldwide. This condition shows the importance of implementing occupational safety and health (K3) in every workplace, including in office environments and construction projects. This community service activity is new because it focuses on the socialization of K3 in the construction project environment as a form of preventive effort against work accidents and work-related diseases. The socialization was carried out at the Kinara Dormitory Development Project on July 20-25, 2024. The purpose of this activity is to increase the knowledge of project workers regarding the importance of K3 and the use of personal protective equipment (PPE), so that they can work more safely and avoid the risk of accidents and PAK. This activity was attended by five workers and was carried out in small groups. The method used was lectures and questions and answers with the help of flipcharts and leaflets. Based on the results of observations, the average worker works for 10 hours per day, six days a week, with a break time of one hour. However, it is known that workers have not used PPE in carrying out their duties. Through this activity, there was an 85% increase in worker knowledge regarding K3 and the use of PPE. Thus, the implementation of K3 is very necessary to create a healthy, safe, and comfortable work environment, as well as to maintain worker productivity. Socialization of occupational safety and health (K3) has been proven to prevent work accidents and occupational diseases (PAK) in the Kinara Dormitory Development Project.